Undergraduate Research: Experiences from the School of Tourism, Cuba - Hernández Flores, Yoan (2023)
In recent years, the articulation of these substantive processes has been achieved in Cuban higher education institutions: teaching, research, and university extension. One of the structures that permit the integration between the previously mentioned processes is the Student Scientific Work Groups. Thus, the authors conducted this research, in which the main objective was to exemplify the role of research in the comprehensive training of university students, taking as a case study the role of FTour in the Faculty of Tourism, University of Havana. Through the bibliographic review of the results of the institution and the workgroup, as well as participatory observation and the results of surveys and interviews made with 35 students, the researchers characterized the general functioning of the investigative process in the country and the institution. This led to an understanding of the context in which the work of the students and teachers who belong to the scientific group is carried out. Moreover, the investigators identified and quantified the results for the establishment of best practices that serve as a reference for the management of this type of scientific group at the country level. The main results indicated the efficiency in the management carried out by students and teachers, which contributes to the comprehensive training of future graduates in tourism. In addition, the importance of the connection between teachers is shown to improve research work between universities and companies. In general, the research demonstrates the importance of FTour in the path traveled during the last five years, which allows it to contribute experiences through the presentation of eight examples of good practices that will allow the comprehensive preparation of the Cuban university population to be achieved. The conclusions are related to transdisciplinarity, motivation from the socialization of scientific results, the training of leaders, the university-company relationship, the insertion in Research Projects, and its link with the research pyramid.